Duration of trade of former communist countries at the EU - Imre Fertő; Károly Attila Soós (Hungarian Academy of Sciences, Institute of Economics, 2008)
The article analyses the duration of exports of individual products of former communist countries to the enlarged European Union (EU25) employing survival analysis. The results show that the duration of trade differs across EU10 and EU15 markets, for the majority of countries the length of trade is higher in EU10 markets than in the EU15 markets. The estimations suggest that differentiated products are traded for more extended periods than homogenous products. In addition, trade relationships starting with large initial sales are more likely to survive the observed five year period than those starting with small values. Finally, the estimations are robust to both markets segments.
Keywords: F10; F14; 330; trade; former communist countries; EU; Internationale Wirtschaftsbeziehungen; EU-Mitgliedschaft; Statistische Bestandsanalyse; Schätzung; EU-Mitgliedschaft; GUS-Staaten